Socio-demographic and obstetric risk factors of anaemia among pregnant women in rural Tamil Nadu - A., Abiselvi; S., Gopalakrishnan; R., Umadevi; R., Rama (International Journal Of Community Medicine And Public Health, 2018)
Background: Anaemia in pregnant women remains one of the most intractable public health problems in developing countries because of various socio-cultural factors like illiteracy, poverty, lack of awareness, cultural and religious taboos, poor dietary habits, and high prevalence of parasitic infestation. The study was aimed at determining the factors associated with anaemia among rural pregnant women in the field practice area of our medical college in Tamil Nadu. Methods: This is a community based cross sectional study among 270 pregnant women registered at our rural health training centre. Ethical approval and informed consent were obtained prior to the data collection. A pilot tested structured interview schedule was used to elicit questions related to socio-demographic and obstetric factors and hemoglobin levels were recorded from their mother child protection card. Various factors associated with anaemic status of the pregnant mothers were analysed using chi square for significance at 95% confidence interval. Results: Among the study participants, 41.5% were found to be anaemic. Passive smoking [kitchen smoke, cigarette/beedi smoke] (p<0.004 and X2-8.2), dietary habits (p<0.009 and X2-6.8), irregular iron folic acid tablet consumption (p<0.0001 and X2-59.1) and deworming (p<0.0001 and X2-12.4) were found to be significantly associated with anaemia. Conclusions: Anaemia is a social problem, wherein the knowledge and attitudes of the pregnant women deeply influence the disease burden. The results suggest that pregnant women and their family members should be educated to understand the importance of anaemia and its associated risk factors.